"WHAT'S BUGGING THE GUT IN OCD?" A REVIEW OF THE GUT MICROBIOME IN OBSESSIVE–COMPULSIVE DISORDER. Issue 3 (2nd December 2015) - Turna, Jasmine; Grosman Kaplan, Keren; Anglin, Rebecca; Van Ameringen, Michael
Abstract : The gut microbiome has become a topic of major interest as of late, with a new focus specifically on psychiatric disorders. Recent studies have revealed that variations in the composition of the gut microbiota may influence anxiety and mood and vice versa. Keeping the concept of this bidirectional "microbiota‐gut‐brain" axis in mind, this review aims to shed light on how these findings may also be implicated in obsessive–compulsive disorder (OCD); potentially outlining a novel etiological pathway of interest for future research in the field.